2013
DOI: 10.1007/s10103-013-1323-4
|View full text |Cite
|
Sign up to set email alerts
|

Potential anti-inflammatory effect of low-level laser therapy on the experimental reflux laryngitis: a preliminary study

Abstract: The most common cause of laryngitis is the laryngopharyngeal reflux disease. The symptoms of laryngitis can be hoarseness, globus, chronic cough, voice fatigue, throat pain, and dysphagia. Low-level laser therapy (LLLT) is beneficial to reduce the pain and inflammatory response without side effects. Therefore, LLLT may be a useful tool for the treatment of laryngitis. This study proposes to analyze the effect of laser therapy in a model of reflux-induced laryngitis. The animals were randomly put into three gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Low-level laser therapy provided a significant decrease in the severity of the inflammatory response in the late phases of wound healing independent of the protocol used. Supporting our findings, similar results have also been reported in the literature (15)(16)(17).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Low-level laser therapy provided a significant decrease in the severity of the inflammatory response in the late phases of wound healing independent of the protocol used. Supporting our findings, similar results have also been reported in the literature (15)(16)(17).…”
Section: Discussionsupporting
confidence: 93%
“…However, a possible role played by intracellular chromophores, such as porphyrins and cytochromes, which are capable of absorbing light energy and converting it into metabolic energy, has been suggested. Thus, LLLT would be able to improve scar repair by direct stimulation of fibroblastic metabolism, promoting an enhancement of the in intracellular levels of adenosine triphosphate and consequently increased protein synthesis, particularly collagen (16). In addition, LLLT promotes important changes in the chemical mediators directly involved in repair, such as reduction of cyclooxygenase-2 (COX-2) expression and consequently the severity of the inflammatory response and increased expression of VEGF, a crucial growth factor for formation of granulation tissue (15,21).…”
Section: Discussionmentioning
confidence: 99%
“…A study using an animal model of reflux laryngitis (a condition including hoarseness, voice fatigue, globus, chronic cough, throat pain, and dysphagia) suggested that the anti-inflammatory effects of PBM may play in the management of this condition [123]. …”
Section: Pbm For the Management Of Orofacial And Neck Complications Omentioning
confidence: 99%
“…[19]. Several RCTs reveal the effectiveness of LLLT in decreasing inflammation, tissue regeneration, and wound healing, especially in diabetic wounds and burn wounds [20][21][22]. Another RCT suggests using 810 nm IR light to accelerate functional recovery regarding the effects of this treatment on nerve injury after surgery [23].…”
Section: Discussionmentioning
confidence: 99%